Postfeminist Commodification of Digital Sexual Labor - Aria, Fahri Mulia; Irawan, Reza Dian; Achmad, Zakaria; Siburian, Adrian David Rafael; Putri, Dian Marisha (Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines how empowerment is marketed through sexual labor performance on digital platforms. Using Mikaela Siragusa, a TikTok and OnlyFans creator, as a case study, it explores how postfeminist ideologies of agency, choice, and self-branding intersect with neoliberal commodification logics. Through discourse and visual analysis of content, captions, and persona supplemented by systematic audience comment analysis, this article argues empowerment is strategically sold within digital marketplaces. Findings reveal how postfeminist rhetoric transforms sexual self-expression into entrepreneurial labor, blurring autonomy and objectification boundaries, while audience participation actively reproduces female sexuality commodification.